First Nations and Inuit Older Adults and Aging Well in Ottawa, Canada - Brooks-Cleator, Lauren Alexandra (Université d'Ottawa / University of Ottawa, 2019)
Urban First Nations and Inuit older adults are aging in a Western-centric sociopolitical environment that is experiencing significant social change due to population aging and urbanization. Consequently, urban communities are facing increasing pressures to respond to the needs of the growing older adult population. As a result of these pressures, older adults are urged to “age well” to reduce their “burden” on society; however, older adults do not all define aging well in the same way and they do not all have the same opportunities to age well. Through my research, I aimed to address a gap in the academic literature concerning urban-dwelling First Nations and Inuit older adults and aging well. Ultimately, my goal was to identify how First Nations and Inuit older adults living in Ottawa could be supported to age well in ways that reflect their urban Indigenous identities, cultural perspectives, and life course. My specific research questions are four-fold: 1) Are Indigenous older adults marginalized through dominant aging well frameworks?; 2) how do community-dwelling First Nations and Inuit older adults (aged 55 years and over) living in Ottawa, Canada, define and negotiate aging well in an urban environment?; 3) what community-level factors contribute to First Nations and Inuit older adults (aged 55 years and over) feeling supported to age well in the city of Ottawa?; and 4) how do community stakeholders in Ottawa produce understandings of supporting urban Indigenous older adults to age well? Informed by a postcolonial theoretical framework, I conducted this research using a community-based participatory research (CBPR) methodology in Ottawa, Ontario, Canada, in partnerships with the Odawa Native Friendship Centre and Tungasuvvingat Inuit. To address my research questions, I conducted semi-structured interviews with nine First Nations older adults, focus groups with 23 Inuit older adults, and photovoice with two First Nations older adults. Additionally, I conducted 13 semi-structured interviews with community stakeholders (i.e., decision-makers and service providers. My doctoral research makes novel contributions to the fields of kinesiology and gerontology by expanding postcolonial theory to issues related to aging research with urban Indigenous older adults; contributing to the emerging literature that brings diverse perspectives into conversations on aging well; challenging assumptions related to urban Indigenous populations and aging well; illustrating the tensions within aging well initiatives that intended to be available for all older adults; and revealing the tensions within efforts to address reconciliation with Indigenous older adults.